Immunomodulatory Effects of Human Mesenchymal Stem Cells on Neutrophil Functions - Maqbool, Maryam (2011)
Polymorphonuclear neutrophil (PMN) are common professional phagocytic cells of the innate immune system. In modern medicine the functions of neutrophils go far beyond the classical phagocytosis and pathogen killing. They perform sophisticated regulatory functions, having implications not only in the inflammatory and immune responses but also in haematopoiesis, wound healing and antimicrobial activities. Neutrophils mediate immune responses that contribute to tissue repair and damage. However, their over activation can lead to detrimental effects. To maintain normal tissue homeostasis, the dual roles of neutrophils are important but they need to be carefully modulated.Mesenchymal stem cells (MSC) are non-haematopoietic, multipotent cells that exert immunomodulatory activity on immune cells. MSC have been shown to interact with innate and adaptive immune cells by modulating their functional responses in vitro and in vivo. The goal of our study was to further build upon these findings by determining the MSC specific immunomodulatory effects on the neutrophil functions. We went about this task by isolating Human neutrophils from whole blood using an optimised Ficoll-dextran method and freshly isolated neutrophils were used in all experiments. Neutrophils in the presence or absence of MSC were assessed for viability, cellular proliferation, chemotaxis, phagocytosis, respiratory burst and apoptosis activities. The multistep optimised isolation method yielded recovery of >50% neutrophils which was confirmed by Leishman staining with purity of >95%. Mesenchymal stem cells significantly (* P<0.05) enhanced the viability of resting and phorbol myristate acetate (PMA) activated neutrophils and simultaneously rescued both resting and PMA activated neutrophil from apoptosis. In terms of neutrophil effector functions MSC significantly (* P<0.05) inhibited opsonised zymosan (OZ) and lipopolysaccharide (LPS) induced neutrophil phagocytosis and also significantly (* P<0.05) inhibited resting, PMA, OZ, fMLP (f-Met-Leu-Phe, N-formylated peptides) and E.coli activated neutrophils respiratory burst. However MSC did not affect neutrophil chemotaxis in either resting or activated state. Similarly in vitro analysis also revealed MSC failed to induce any changes in basal cell proliferation activity of neutrophil. Overall the results reveal that MSC have an immunosuppressive effect on neutrophil survival, apoptosis, phagocytosis and respiratory burst activity. These findings display the efficiency of MSC in limiting the hostile effects of neutrophils. Consequently this study makes a compelling case for the use of MSC as a therapeutic tool for the treatment of neutrophil mediated immune disorders.